Modern examination methods and pathogenesis for the detection of entereviruses (Progress Annals: Journal of Progressive Research, 2024)
The article presents modern information about the etiology, epidemiology, and clinical manifestations of enterovirus infection in children and adults. Issues of differential diagnosis, the use of laboratory research methods, treatment and prevention of infection are considered.